2022
DOI: 10.2147/idr.s357997
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Acute Kidney Injury in Covid-19 Patients- Retrospective Single-Center Study

Abstract: Introduction In December 2019, a coronavirus disease 2019 (COVID-19) disease outbreak started in Wuhan, Hubei Province, China, and spread rapidly to other regions of the world. Although diffuse alveolar injury and acute respiratory failure were the most prominent characteristics, further investigation of organ involvement is essential. Aim In this study, we aim to determine the prevalence of acute kidney injury (AKI) in covid-19 patients and also the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
1
8
0
2
Order By: Relevance
“…Statistical Power Analysis: Our initial power analysis, based on expected AKI prevalence and effect size, indicated that our sample size was sufficient. This is supported by the prevalence rates reported in the literature, which vary significantly: Bashir et al (2022) found a 12.7% prevalence in their study, highlighting the lower end of the spectrum [ 14 ]. Morosini et al (2021) observed a prevalence of 37.14%, demonstrating the higher variability in different patient populations [ 64 ].…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Statistical Power Analysis: Our initial power analysis, based on expected AKI prevalence and effect size, indicated that our sample size was sufficient. This is supported by the prevalence rates reported in the literature, which vary significantly: Bashir et al (2022) found a 12.7% prevalence in their study, highlighting the lower end of the spectrum [ 14 ]. Morosini et al (2021) observed a prevalence of 37.14%, demonstrating the higher variability in different patient populations [ 64 ].…”
supporting
confidence: 62%
“…Several factors could explain this wide range. In this sense, the development of AKI in patients with COVID-19 has been associated with different variables, including smoking, increased levels of C-reactive protein (CRP), the extent of lung involvement, high leukocyte count, and the requirement for mechanical ventilation [ 14 , 15 , 16 ]. In studies conducted in the United States, additional characteristics include male gender, advanced age, African American ethnicity, and comorbidities such as diabetes, hypertension, cardiovascular illnesses, congestive heart failure, and a high body mass index [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were observed in a study conducted in Somalia, Mogadishu. 17 This similarity may be explained by the two populations’ similar lifestyles and economic status.…”
Section: Discussionmentioning
confidence: 99%
“…The SARS-CoV-2 virus infection is linked to high levels of proinflammatory markers; they have been analyzed in order to determine whether they could be informative with regard to the outcome of the disease. From a nephrology point of view, numerous studies were carried out in relation to COVID-19-related acute kidney injury (AKI); indeed, around 1 in 10 of hospitalized patients with COVID-19 experience AKI [ 2 ]. In addition, it was shown that AKI was a serious risk factor for the outcome; however, there is a wide variation in the incidence and the outcomes being reported [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…From a nephrology point of view, numerous studies were carried out in relation to COVID-19-related acute kidney injury (AKI); indeed, around 1 in 10 of hospitalized patients with COVID-19 experience AKI [ 2 ]. In addition, it was shown that AKI was a serious risk factor for the outcome; however, there is a wide variation in the incidence and the outcomes being reported [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%